2023
DOI: 10.1111/aogs.14505
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling of pregnancies complicated by preeclampsia: A longitudinal study

Abstract: Introduction Preeclampsia is associated with maternal metabolic disturbances, but longitudinal studies with comprehensive metabolic profiling are lacking. We aimed to determine metabolic profiles across gestation in women who developed preeclampsia compared with women with healthy pregnancies. We also explored the respective effects of body mass index (BMI) and preeclampsia on various metabolic measures. Material and methods We measured 91 metabolites by high‐throughput nuclear magnetic resonance spectroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…In relation to our previous study on metabolic differences in pre-eclamptic pregnancies, 7 we observed a resemblance between the metabolic profiles of women with overweight/obesity in early pregnancy and those found in late pregnancy of late-onset preeclampsia, especially regarding particle concentration of the largest VLDL and triglycerides. Kivelä et al found that GDM, pre-eclampsia, and chronic hypertension were associated with metabolic alterations similar to obesity.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…In relation to our previous study on metabolic differences in pre-eclamptic pregnancies, 7 we observed a resemblance between the metabolic profiles of women with overweight/obesity in early pregnancy and those found in late pregnancy of late-onset preeclampsia, especially regarding particle concentration of the largest VLDL and triglycerides. Kivelä et al found that GDM, pre-eclampsia, and chronic hypertension were associated with metabolic alterations similar to obesity.…”
Section: Discussionsupporting
confidence: 75%
“…The metabolism of women with overweight and obesity was characterized by less accentuated increase in lipids but exaggerated increase in glucose and insulin compared to normal‐weight women. By detailed metabolic characterization of healthy pregnant women compared to women with late‐onset pre‐eclampsia, we showed differences in metabolites between these two groups already in early pregnancy 7 . Near term, women with pre‐eclampsia developed a metabolic profile that resembled the metabolic alterations observed in atherosclerotic disease, including elevated levels of total lipids, very‐low‐density lipoprotein (VLDL), triglycerides, and total fatty acids.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Recent epidemiological evidence suggests that there are common risk factors between PTB and cardiovascular disease 11 . Women who experience PTB have a twofold higher risk of developing cardiovascular disease later in life compared to those who have full-term deliveries 12 .…”
Section: Introductionmentioning
confidence: 99%